Sanitation control of some equipments used in poultry slaughterhouse line - Çetinkaya, Nilgün; Iincili, Gökhan Kürşad; Arslan, Ali (Refik Saydam National Public Health Agency (RSNPHA), 2020)
Objective: Microbial contamination of chicken meat varies depending on various processes applied during production, slaughtering and processing. This study was carried out to investigate the effectiveness of sanitation (cleaning+disinfection) implemented in a commercial poultry slaughterhouse in Elazig. Methods: For this purpose, swab samples from defeathering machine fingers, outlet band of water cooling tank, outlet band of air cooling and end product band of diet department were taken to analyze the number of total mesophilic aerobic bacteria (TMAB), coliforms, Enterobacteriaceae and the prevalence of Salmonella spp. before sanitation and at the 20 and 30 minutes after sanitation process. Results: Total mesophilic aerobic bacteria numbers of the samples taken from fingers of mechanical defeathering machine before sanitation and at the 30 minutes after sanitation process were 5.69±0.83, and 4.64±0.83 log10cfu/cm2, and the differences between before and after sanitation were significant (p <0.05). In addition, it was determined that the differences of the total mesophilic aerobic bacterica counts between before and after sanitation in the water cooling outlet band, air cooling outlet band and the diet product final product band were significant (p<0.05). Enterobacteriaceae numbers of the samples taken from fingers of mechanical defeathering machine before sanitation and at the 20 and 30 minutes after sanitation process were 4.00±2.09, 2.43±0.58 and 3.27±0.69 log10 cfu/cm2, in the samples taken from outlet band of water cooling tank were 2.74±0.82, 1.47±1.35 and 0.32±0.86 log10 cfu/cm2, respectively. Coliform bacteria number of the samples taken from end product band of diet department before sanitation and at the 20 min after sanitation process were 2.44±0.81 and 1.65±1.43 log10 cfu/cm2, respectively, no coliform bacteria was detected at the 30 min after sanitation process. The prevalence of Salmonella spp. in the samples taken from defeathering machine fingers before sanitation and at the 20 and 30 minutes after sanitation process were 66.67%, 33.33% and 16.67%, respectively. Salmonella spp. was detected in 8.33% of the samples taken from outlet band of water cooling tank and air cooling. Salmonella spp. was not detected in the samples taken from the end product band of diet department at any time. Conclusion: As a result, it can be speculated that the cleaning and sanitation process implemented in the related establishment is satisfactory, however, extending shelf life of the products and eliminating the poultry meat-borne pathogenic microorganisms that threaten public health, performing better sanitation process may be recommended. © 2020 Refik Saydam National Public Health Agency (RSNPHA).
Keywords: Enterobacteriaceae; Poultry; Salmonella spp.; Sanitation; Slaughterhouse